PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENDIDIKAN ALAM (IPA) Penelitian Tindakan Kelas pada Siswa Kelas V SDN Barunagri, Lembang - Nuri Annisa (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
This research has been drawn from a concern on low students’ test achievement in science lesson at SDN Barunagri Lembang. A Classroom Action Research (CAR) method with three cycles of planning, acting, and reflecting was conducted to try out an inquiry teaching approach in order to increase students’ achievement. Fourty seven (47) students of SDN Barunagri Lembang were involved in this study. The results of this study showed that at every cycle there was an increase in students’ achievement. At the first cycle, classroom average of the achievement was 61,1 with only two students reach the minimum achievement standards. At the second cycle, the classroom average was shown to be 73,5 with 31 students achived the minimunum standards. At last, the third cycle, the classroom avverage has significanlty increased to 82,3 with 36 students or 77% have reached the minimum standrad. In conclusion the application of inquiry’s method is able to improve the activities and students learning achievement. DOI: 10.15408/tjems.v1i2.1270